Model Program Intervensi Anti Bullying Berbasis Sekolah - Dian Ayu Zahraini (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2019)
AbstractThis research is a learning model for anti-bullying program for the school-based early childhood stages beginning with a needs analysis which later developed learning models, and construct a draft model of learning. The study begins with a preliminary study that is the study of the theory and the findings of previous studies, followed by draft learning model. The final stage is the preparation of the guide book learning model prototype anti-bullying school-based program.The results showed that young children can develop an understanding of bullying, adaptation to classroom rules against bullying, understanding of what people feel about bullying and the basic rules in the anti-bullying program, as well as the goldern rules in the Playground. The implementation of the model of anti-bullying programs in schools in Â RA At Thohirriyah showed a positive response in which children can develop an understanding of the pre-reading the question, the question of post-reading, post-reading activities, and understanding of emotions as the process of developing their social skills. Keywords: Learning, Anti-Bullying, School Based